Strategi Pengembangan UMKM Kopi Melalui Business Model Canvas dan Pendekatan Swot: (Studi Kasus Toko Kopi Paul di Tajurhalang Kabupaten Bogor) - Tika Kartika Asri; Tyara Poernomo Putri; Mujito Mujito; Dwi Oktiana Irawati (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the development strategy of micro, small, and medium enterprises (MSMEs) in the coffee sector using the Business Model Canvas (BMC) and SWOT Analysis approaches. A case study was conducted at Paul Coffee Shop, located in Tajurhalang, Bogor Regency. The research method employed was descriptive qualitative, with data collected through observation, interviews, and literature review. The results indicate that the current business model of Paul Coffee Shop has strengths in affordable pricing and personal relationships with customers but still has weaknesses in digital marketing and product innovation. Through SWOT analysis, development strategies were formulated, including product diversification, strengthening digital marketing, collaboration with local MSMEs, and customer loyalty programs. This study emphasizes that BMC can be used not only in the initial stage of business establishment but also as a tool for evaluation and strategy development for ongoing MSMEs.